2013
DOI: 10.1177/0021909613510132
|View full text |Cite
|
Sign up to set email alerts
|

Teachers’ Understanding and Conceptualisation of the HIV and AIDS Policy: The Case of Secondary Schools in Zimbabwe

Abstract: This study examined secondary school teachers’ understanding of the HIV and AIDS education policy and curriculum in Zimbabwe. The study was informed by the Concerns-Based Adoption Model. Twenty teachers, four school heads from the participating schools and two Ministry of Education officials from Masvingo provincial offices participated in the study. Data for the qualitative case study were collected via individual interviews, focus group interviews and open-ended questionnaires. The study found that teachers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…Some religions believe that CSE defiles children. In addition, it is construed as taboo to talk about, especially to children who have not yet attained adolescence (Gudyanga et al, 2019;Mugweni et al, 2013), hence inappropriate for young children. Consequently, attempts to teach the CSE content are resisted by most Zimbabweans.…”
Section: Introductionmentioning
confidence: 99%
“…Some religions believe that CSE defiles children. In addition, it is construed as taboo to talk about, especially to children who have not yet attained adolescence (Gudyanga et al, 2019;Mugweni et al, 2013), hence inappropriate for young children. Consequently, attempts to teach the CSE content are resisted by most Zimbabweans.…”
Section: Introductionmentioning
confidence: 99%
“…Some trained teachers were not aware of how to teach the G&C subject (World Bank, 2002), while others reported that they were shy to teach some topics, for instance sexuality education. They argued that such topics clashed with their cultural values and beliefs, that sex was taboo to talk about, for instance, that the vernacular for human reproductive organs is taboo (Mugweni, Hartell, & Phatudi, 2013). All these issues compounded teachers’ failing to teach G&C and sexuality education within HIV and AIDS education.…”
Section: Introductionmentioning
confidence: 99%
“…In light of this, this scenario becomes a dilemma, and, hence, a challenge to the teacher to be sensitive to the different cultures. Clearly, culture plays a key role in teaching sexuality education (Mugweni et al., 2013) and might prohibit teaching the skills to negotiate safer sex (Mugweni et al., 2013). The Zimbabwean black girl, for example, should not initiate sex, let alone safer sex, because of her cultural upbringing (Muguwe & Gwirayi, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous ethical considerations were made throughout the data collecting process for this research, since data collection is always a costly undertaking. According to Mugweni (2012), ethics is a philosophy of morals concerned with forming judgments about what is bad or good, appropriate, or not appropriate, acceptable or unacceptable, wrong or right Cohen, Manion, and Morrison (2007) demonstrate that recent advances research in social science research have put a premium on ethical concerns, with investigators obligated to honour and safeguard individuals engaged or impacted by their study. The investigator considered the following: et al (1996) argue that a critical aspect of student research is ensuring that participants understand the task at hand and are informed of any possible negative implications of involvement.…”
Section: Ethicsmentioning
confidence: 99%